Kontribusi Pembiasaan Menghafal Juz 30 Al Qur'an Dan Sholat Dhuha Terhadap Penguatan Karakter Religius Siswa Kelas V SD Aisyiyah Unggulan Gemolong Tahun 2016/2017 - Rahmawati, Vernanda; , Honest Umi Kaltsum, SS., M.Hum (2017)
This study aims to determine the contribution of: (1) habituation memorizing 30 Juz of the Qur'an to the strengthening of the religious character of fifth grade students of SD Aisyiyah seed Gemolong, (2) Duha prayer to the strengthening of the religious character of fifth grade students of SD Aisyiyah seed Gemolong, and (3) habituation memorize Juz 30 Quran and Duha prayer to the strengthening of the religious character of fifth grade students of SD Aisyiyah seed Gemolong. This research is descriptive quantitative. Fifth grade elementary school student population, main Aisyiyah Gemolong. Total sample of 30 students drawn randomly. Sampling techniques using simple random sampling. The technique of collecting data using questionnaires and documentation. Data analysis techniques using multiple regression test. Based on the multiple linear regression equation: Y = 8,977 + 0,152 X1 + 0,264 X2. The results of the data analysis with a significance level of 5% was obtained: (1) there is a contribution of habituation memorizing 30 Juz of the Qur'an to the strengthening of the religious character of students. Proven t > t table (3,423 > 1,701) and the significance of 0,002 < 0,05. (2) There is Duha prayer refraction contribution to the strengthening of the religious character of students. Proven t> t table (3,031 > 1,701) and the significance of 0,005 < 0,05. (3) memorizing 30 Juz of the Qur'an and pray Dhuha contribute to the strengthening of the religious character of students. Proven Fcount > Ftable (8,977> 3.35) and the significance of 0,048 < 0,05.